2020
DOI: 10.1016/j.scitotenv.2020.137190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NH3 and alkaline metals on the formation of particulate sulfate and nitrate in wintertime Beijing

Abstract: Nitrate Ammonia Alkaline metals of H 2 SO 4 and HNO 3 to form particulate SO 4 2− and NO 3 −. The relationships between mass fractions of SO 4 2− and NO 3 − in those ranges of different alkaline metal ion content also suggested that alkaline metal ions participate in the competing neutralization reaction of sulfate and nitrate. The implication of the current study is that in some regions the chemistry to incorporate sulfur and nitrogen into particle phase might be largely affected by desert/fugitive dust and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 84 publications
2
19
0
Order By: Relevance
“…This same finding was observed in a field study conducted in Tianjin during the years 2014–2015 . Alkaline-earth metals including Ca 2+ and Mg 2+ could serve as sinks of acidic species (e.g., SO 4 2– ) . Source contribution to α H+ observed in winter exhibited a different pattern than when compared to autumn.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This same finding was observed in a field study conducted in Tianjin during the years 2014–2015 . Alkaline-earth metals including Ca 2+ and Mg 2+ could serve as sinks of acidic species (e.g., SO 4 2– ) . Source contribution to α H+ observed in winter exhibited a different pattern than when compared to autumn.…”
Section: Resultssupporting
confidence: 79%
“…22 Alkalineearth metals including Ca 2+ and Mg 2+ could serve as sinks of acidic species (e.g., SO 4 2− ). 58 Source contribution to α H+ observed in winter exhibited a different pattern than when compared to autumn. The greatest averaged source contribution of α H+ was observed to be IS (45%), followed by BB (18%), SS (16%), MS (13%), and DS (8%) in winter 2019.…”
Section: Mobile Source (Ms)mentioning
confidence: 89%
“…Observational studies have concluded that nitrate production is favored under a high pH. 35 Many SOA formation pathways are acid-catalyzed, and thus, it is believed that acidic particles can promote SOA formation thereon. 15,53,61 Dust aerosols are rich in alkaline metals, which would typically lead to a high pH, theoretically prohibiting reactions that require acidic environments.…”
Section: Occurring After N I G H T T I M E F O G S T H E V O L U M E...mentioning
confidence: 99%
“…11 More recent results suggest that alkaline metal ions in dust can promote sulfate formation by increasing aerosol pH. 13,35,36 Size-resolved aerosol chemical compositions were typically measured using aerosol mass spectrometers that only covered submicron aerosol particles, 3 which cannot adequately reflect the formation of SA components on dust particles that are mostly coarse particles in the size range of 0.8−30 μm. 37,38 Thus, the role of dust in severe haze development remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia is an important constituent of trace particles in the atmosphere, and forms aerosols during reactions with pollutants such as sulfuric and nitric acid [1]. It is a colorless alkaline chemical compound and has a pungent smell [2]. Ammonia is highly soluble in water with solubility of 31% w/w [3].…”
Section: Introductionmentioning
confidence: 99%